Conceptualisations of personal growth in Ghanaian Orthodox Christians - Remmerfelt, Emelie (Mental health, religion & culture, 2021)
Personal growth is integral to mental health. Hegemonic psychological theories about personal growth were formulated in an individualistic culture where people experience an independent self. Conceptualisations of personal growth may be different in collectivistic cultures where people experience an interdependent self. Ghanaian Orthodox Christians are embedded in a collectivistic culture where religion permeates every-day life. The aim of this study was to investigate how Ghanaian Orthodox Christians conceptualise personal growth. We interviewed 12 participants from the University of Ghana who belonged to different Orthodox Christian Churches. The results showed that the participants wanted material success, and they acknowledged that this takes effort. Relationships were facilitating their ambitions, and for that reason learning to adapt to social norms was important. Most important of all was their relationship to God. The results implied a conceptualisation of personal growth that relies on an interdependent experience of the self.